Simulation and gaming for mathematical education epistemology and teaching strategies - Piu, Angela, 1971-; Fregola, Cesare; IGI eBooks; IGI Global (Hershey, Pa. : IGI Global (701 E. Chocolate Avenue, Hershey, Pennsylvania, 17033, USA), 2011)
"This book proposes simulation games supported by the most recent discoveries and advances in theories of learning research, and gears operational decisions toward the development of an integrated system for the teaching of mathematics in primary schools"--Provided by publisher.
1. Epistemological framework and mathematical learning / Cesare Fregola -- 2. Towards the construction of a system of maths teaching / Daniela Peja -- 3. Simulation games / Carmelo Piu -- 4. Simulation games for the learning and teaching of mathematics / Angela Piu -- 5. Simulation games and emotive, affective and social issues / Cesare Fregola -- 6. Theoretical reflections on the construction of simulation games / Daniela Peja -- 7. Methodological proposals for simulation games / Cesare Fregola -- 8. Design of a simulation game for the learning of mathematics / -- Angela Piu -- 9. Description of games / Angela Piu, Cesare Fregola, Anna Santoro -- 10. The conduct of a simulation game / Roberta Masci -- 11. A review of previous studies / Angela Piu -- 12. Research outline / Angela Piu -- 13. Research results / Angela Piu, Cesare Fregola, Claudia Abundo, Salvatore Fregola.
Includes bibliographical references.
Also available in print.
Mode of access: World Wide Web.
Title from ebook home page (viewed on Sept. 23, 2010).
Keywords: Mathematics -- Study and teaching (Primary) -- Simulation games; Simulation games in education; Construction of mathematical concepts; Design of simulation games; Epistemological framework; Future developments in simulation; Gaming for mathematical education; Isometries; Mathematical learning; Mathematization in the virtual age; Simulation for mathematical education; Teaching strategies with simulation; Electronic books